Regional revenue management program sustainable development objectives environmental sector Indonesian SEZs - Edi Yanto; Risman Risman; Andi Naharudin; Bustari Bustari; Yahya Yahya (International Journal of Applied Finance and Business Studies, 2023)
The Sustainable Development Goals Program is the implementation of a culture of sustainable development in a country by taking into account environmental, social, and economic aspects. The Tolitoli area serves as a buffer for the SEZ in Palu City, and the Environmental Service runs a waste management program related to optimizing retribution revenue. With a quantitative descriptive approach through table analysis and trend analysis techniques, the performance of retribution management will be known. The results of the study show that the revenue budget target increases annually by 31.59%. Revenue achievements for 2020–2022 were 105%, 94%, and 78%, respectively, which showed that performance was not optimal due to a decrease in income patterns and that in the last 2 years it did not reach the target